Kontribusi Motivasi dan Disiplin Kerja terhadap Pencapaian Kinerja Karyawan di PT. Pegadaian Kanwil III Palembang - Duwi Mariska; Kholilah (MOTIVASI, 2025)
Purpose – This study aims to determine the effect of motivation and work discipline on the performance of employees of PT Pegadaian Kanwil III Palembang. Design/methodology –The type of research used is associative research. The independent variables in this study are motivation and work discipline, while the dependent variable is employee performance. The population in this study were all permanent employees at PT Pegadaian Kanwil III Palembang, totaling 82 people, with a sample of 45 respondents using the Slovin formula 10%, with sampling techniques using simple random sampling. Primary data in this study were obtained from questionnaires, while secondary data were obtained from documentation. The data analysis techniques used are classical assumption test analysis, multiple linear regression, hypothesis testing (F test and t test), and the coefficient of determination. Findings -The results of the F test (simultaneous) prove that there is a significant influence between motivation and work environment on the performance of employees of PT Pawnshop Regional Office III Palembang. The results of the t test (partial) prove that there is a significant influence between motivation on employee performance, and there is a significant influence between work discipline on the performance of employees of PT. Pawnshop Regional Office III Palembang. The coefficient of determination shows that motivation and work discipline are able to contribute to improving employee performance by 67.4%.